THE IMPORTANCE OF MINERAL AND ORGANIC FERTILIZERS IN THE CULTIVATION OF MEDICINAL BERBERIS OBLONGA SEHNEID (Scientific journal of the Fergana State University, 2025)
The article presents biological properties, chemical composition, application in folk medicine, as well as scientific basis for the use of organic and mineral fertilizers.